The long shadow of Vatican II: living faith and negotiating authority since the Second Vatican Council - Rompay, Lucas van; Miglarese, Sam; Morgan, David (University of North Carolina Press, 2015)
Is there reason for hope?: The Second Vatican Council and Catholic irreligious relations / Leo D. Lefebure -- The American reception and legacy of The Second Vatican Council / Leslie Woodcock Tentler -- The exercise of ecclesial authority in the light of Vatican II / Catherine E. Clifford -- Vatican II and the history of interpretation: the case of Roman Catholic womenpriests / Jill Peterfeso -- Quebec's wayside crosses and the creation of contemporary devotionalism / Hillary Kaell -- Epilogue / Lucas van Rompay, Sam Miglarese, and David Morgan.